Factors related to the success in women's football-a systematic review - Wang, S.; Shen, M.; Li, P.; Liu, H. (Frontiers in Sports and Active Living, 2025)
Introduction: Football success is defined as the achievement of a team in the game, which is measured by the combination of winning championship, higher ranking and better performance. This study reviews the factors influencing the football success in women's football from macro (economy, politics, culture), meso (geographical environment, football tradition, talent development, gender equality, league prosperity), and micro (technical/tactical, physical performance, situational factors) perspectives.